Tools for participatory design of agricultural index insurance supported projects reaching over one million households in several African countries - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The International Research Institute for Climate and Society (IRI), supported by CCAFS, expanded the reach of tools for participatory design of agricultural index insurance, supporting projects reaching over one million households. In 2020-2021, these tools enabled local partners to make data-driven decisions about index insurance contracts on a scale deeper and wider than ever before. These tools supported projects that reached one million farmers in multiple countries through collaboration with the government of Zambia, the World Food Programme, and others.